Characteristics of solar thermal absorber materials for cross absorber design in solar air collector - Abdul Majid, Zafri Azran; A. Razak, Amir; Ruslan, M.H; Sopian, Kamaruzzaman (Universiti Malaysia Pahang Publisher, 2015)
The solar thermal absorber is an integral component of a solar air collector, especially in determining the overall performance of a solar air thermal system. The type and shape of material will have a direct impact on the operating temperature and thermal energy storage effect of the solar air thermal collector. This paper focused on the investigation of aluminum and stainless steel hollow square rods in terms of their solar thermal absorber performance. Comparisons between different materials and coatings were conducted in order to determine their impact in solar thermal absorber applications. Experiments were conducted on both materials with flat-black coated and non-coated surfaces of aluminum (6063) and stainless steel sets respectively. Both sets were exposed under 585 W/m2 radiation and the temperature response was recorded. A significant improvement was shown to result from the application of flat-black coating against non-coated material, with maximum temperatures of 67.2oC and 48.3oC respectively. It was observed that for the hollow square metal absorber the heating and cooling characteristics can be established by means of the relation between the surface and inner air temperatures of the absorber. This method can assist in temperature profiling of hollow square metal for solar thermal application.